IgE to the Mammalian Oligosaccharide Galactose-α-1, 3-Galactose Is Associated With Increased Atheroma Volume and Plaques With Unstable Characteristics—Brief Report. Issue 7 (July 2018) - Wilson, Jeffrey M.; Nguyen, Anh T.; Schuyler, Alexander J.; Commins, Scott P.; Taylor, Angela M.; Platts-Mills, Thomas A.E.; McNamara, Coleen A.
Abstract : Objective—: Emerging evidence suggests a link between coronary artery disease and type 2 immunity. We sought to test the hypothesis that IgE sensitization to the mammalian oligosaccharide galactose-α-1, 3-galactose (α-Gal)—the target allergen of delayed anaphylaxis to red meat—is associated with coronary artery disease. Approach and Results—: Total IgE and specific IgE to α-Gal were assayed on sera from 118 subjects who presented for cardiac catheterization and underwent intravascular ultrasound. IgE to α-Gal was detected in 26%, and atheroma burden was higher in sensitized subjects ( P =0.02). Because α-Gal sensitization relates to an environmental exposure that could be a risk factor for early-onset coronary artery disease (ie, tick bites), we age stratified the cohort. In subjects ⩽65 years of age, the strength of the association with atheroma burden was stronger ( P <0.001), and plaques in the sensitized group had less stable features based on intravascular ultrasound. To address the specificity of the association with IgE to α-Gal, IgE to inhalants and peanut were assayed and were not associated with coronary artery disease. Total IgE and α-Gal–specific IgE were strongly associated with each other, but the strength of the relationship with atheroma burden was stronger for α-Gal–specific IgE. This association was significant when adjusted for sex, diabetes mellitus, hypertension, statin use, and total IgE (regression coefficient, 12.2; SE, 5.2; P =0.02). Conclusions—: Increased atheroma burden and plaques with more unstable features were associated with IgE to α-Gal—an effect most pronounced in subjects ⩽65 years of age. IgE sensitization to α-Gal may represent a novel, and potentially modifiable, risk factor for coronary atherosclerosis. Abstract : Supplemental Digital Content is available in the text.